Hubungan tingkat pendidikan, status pekerjaan, dan perbedaan rerata asupan makanan ibu hamil: Studi cross-sectional pada ibu hamil di Provinsi Sumatera Barat - Fristy Dwinanda Ralni; Nur Indrawati Lipoeto; Zurayya Fadila (Faculty of Medicine, Universitas Andalas, 2026)
Relationship between education level, employment status, and differences in average food intake among pregnant women: A cross-sectional study on pregnant women in West Sumatra Province A pregnant woman will experience weight gain. Many factors influence weight gain in pregnant women, such as level of education, employment status, and food intake. Objective: To determine the relationship between education level, employment status, and variations in average dietary intake on weight gain among pregnant women. Methods: A cross-sectional study was conducted in West Sumatra Province with 183 respondents. Data on pregnant women's weight, employment status, education level, and food intake were obtained from secondary data sources, including maternal weight measurements, sociodemographic data, and the SQ-FFQ. The analysis uses the Chi-square test and one-way ANOVA. Results: The relationship between education level and employment status with weight gain of pregnant women were obtained with values of p=0.661 and p=0.977, and the difference between the average food intake (energy, carbohydrates, protein, and fat) with the weight gain of pregnant women was obtained sequentially, with values of p=0.179, 0.568, 0.143, and 0.104. Conclusion: There was no significant relationship between job status and education level and weight gain of pregnant women, and there was no significant average difference between food intake and weight gain of pregnant women. Keywords: education level, employment status, food intake, pregnancy weight gain